Musical childhoods of Asia and the Pacific - Lum, Chee Hoo; Whiteman, Peter (Advances in music education research., 2012)
Musical Childhoods of Asia and the Pacific agglomerates stories of young children's music and musicking from around Southeast Asia and the Pacific. A collection of truly unique traditions are interrogated through a variety of contemporary methodologies. Readers are privileged to hear about children's musical worlds from children, mothers' musical worlds from mothers, a struggle to engage with music in a closed society, and new gender politics, among other stories. Researchers share experiences and insights gained from applying their chosen methodologies and add to the debate that shapes the continually transforming domain of music education research.Musical Childhoods builds on the diverse inquiry presented in the first three volumes in the series. This volume is an important addition to the libraries of colleges of education and schools of music, as well as music scholars and educators, researchers, and graduate students who are concerned with advancing both the scope and quality of research in the study of music teaching and learning.